2019
DOI: 10.1016/j.apnum.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Linear instability of the Peregrine breather: Numerical and analytical investigations

Abstract: We study the linear stability of the Peregrine breather both numerically and with analytical arguments based on its derivation as the singular limit of a single-mode spatially periodic breather as the spatial period becomes infinite. By constructing solutions of the linearization of the nonlinear Schrödinger equation in terms of quadratic products of components of the eigenfunctions of the Zakharov-Shabat system, we show that the Peregrine breather is linearly unstable. A numerical study employing a highly acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As for more complex and fundamental higher-order NLSE solutions on a condensate, in its core there is still an integrable NLSE. Therefore, NLSE-based techniques can be inherently useful for analysis of the solutions, such as a higher-order Akhmediev-, Kusnetsov-Ma, and Peregrine-type solutions [36][37][38][39][40], which will be our work in future. Therefore, NFT provide an alternative way to describe solitons in general, which compliments temporal and spectral measurement.…”
Section: Resultsmentioning
confidence: 99%
“…As for more complex and fundamental higher-order NLSE solutions on a condensate, in its core there is still an integrable NLSE. Therefore, NLSE-based techniques can be inherently useful for analysis of the solutions, such as a higher-order Akhmediev-, Kusnetsov-Ma, and Peregrine-type solutions [36][37][38][39][40], which will be our work in future. Therefore, NFT provide an alternative way to describe solitons in general, which compliments temporal and spectral measurement.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Voronovich et al confirmed numerically that the bottom friction effect, even when it is small in comparison to the nonlinear term, could hamper the formation of a breather freak wave at the nonlinear stage of instability [134]. Investigations on linear stability demonstrated that the Peregrine soliton is unstable against all standard perturbations, where the analytical study is supported by numerical evidence [135][136][137][138].…”
Section: The Peregrine Solitonmentioning
confidence: 94%
“…Investigations on linear stability demonstrated that the Peregrine soliton is unstable against all standard perturbations, where the analytical study is supported by numerical evidence. [145][146][147][148].…”
Section: The Peregrine Solitonmentioning
confidence: 99%